Role of gambogenic acid in regulating PI3K/Akt/NF-kβ signaling pathways in rat model of acute hepatotoxicity. Issue 3 (20th January 2021) - Ding, Zhongyang; Li, Ying; Tang, Zhangfeng; Song, Xiaoyi; Jing, Fa; Wu, Haotian; Lu, Bei
ABSTRACT: The purpose of this study is to investigate the protective effect of gambogenic acid (GA) in acetaminophen (APAP)-induced hepatotoxicity in rat models. GA (10 mg/kg) was administered intraperitoneal (i.p.) to rats for 7 consecutive days followed by APAP (500 mg/kg) single dose (i.p.) on the final day after GA administration. The levels of MDA, GSH, SOD, CAT, GPx, GST, ALP, AST, ALT, proinflammatory cytokines (TNF-α, IL-1β, IL-6), apoptosis markers (caspase-3 and -9, Bax, Bcl-2), 4-hydroxynonenal (4-HNE), and prostaglandin E2 (PGE2 ) were evaluated. Results exhibited protective effects of GA by inhibiting inflammation, preventing oxidative stress and apoptosis in APAP-induced liver. Histopathological changes caused by APAP were attenuated, protein expressions of phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) were upregulated, and nuclear factor–kappa β (NF-kβ) was downregulated by GA. In summary, GA significantly exerted anti-inflammatory and antiapoptotic effects against APAP-induced hepatotoxicity potentially through regulation of PI3K/Akt and NF-kβ signaling pathways. Graphical Abstract: